Pembentukan Konsep Diri Anak yang Putus Sekolah (Studi Empiris di Jatinangor, Kabupaten Sumedang) - Amara Lestiantri; Fauziah Putri; Novia Agustin Asqolani (Epistemik Press, 2020)
Jatinangor can be categorized as an educational area because it contains several leading campuses. Among them are ITB, IPDN, IKOPIN, and UNPAD. But who would have thought that behind all that there were still a lot of early childhood dropouts in Jatinangor. This is very worrying because in fact, even in educational areas such as Jatinangor, cases like this occur. One of the factors in the formation of self-concept is education. Education plays an important role because it can affect how a person's character is formed in the future. Therefore, the author is interested in studying how the formation of self-concept of children who drop out of school, especially in Jatinangor. According to our observations, there are differences in character between children who go to school and children who drop out of school. Although we realize that we cannot generalize, most of the children who drop out of school tend to be hampered in the formation of their self-concept.